Modal Sosial Kelompok Pengolah Dan Penjual Jamu Dalam Pengembangan Objek Wisata Kampung Pejabat Kota Banjarbaru - Wardani, Ega; Ruswinarsih, Sigit; P, Reski (Universitas Lambung Mangkurat, 2024)
Jamu processors and sellers group in Kampung Pejabat tourism object have the potential of social capital for the development of tourism objects. This study aims to find out the elements of social capital owned by the jamu processors and sellers group in Kampung Pejabat tourism object. The method used in this research is qualitative. The data source technique using purposive sampling and informants in this study revealed six people. Data collection techniques were carried out by observation, interviews and documentation. The data analysis technique used in this research is to reduce the data, present the data and draw conclusions. Testing the validity of the data using triangulation techniques. The results of this study found that the elements of social capital owned by jamu processors and sellers group in Kampung Pejabat tourism object include a) trust; which consists of ascriptive beliefs and processual beliefs b) norms; which is formed from spatial similarity, common identity and common purpose c) social networks; there are bonding social capital, bridging social capital and linking social capital.